Analisis Index Maslahat Peran UMKM Dalam Meningkatkan Kesejahteraan Masyarakat: Studi Kasus UMKM Keripik Cipuy Desa Nanggerang - Irwan, Sendrika Devis; Junaedi, Dedi; Salistia, Faisal (As-Syirkah: Islamic Economic & Financial Journal, 2022)
This study aims to determine the role of micro, small and medium enterprises (MSMEs) in improving the welfare of the community from the perspective of Islamic economics. The background is that many people in Nanggerang Village whose economy is still in a lower middle class condition are in difficulty in meeting family welfare. This type of research uses descriptive qualitative. The selection of informants was carried out using the Purpose Sampling technique. The types of data are primary data and secondary data collected through observation, interviews, questionnaires and documentation. The validity of the data was tested through the source triangulation technique. Then the data analysis techniques used in this study are data collection, data reduction, data presentation, and data verification (drawing conclusions). The results showed that the Cipuy Chips UMKM in Nanggerang Village had a role in improving the welfare of the community from a sharia economic perspective measured by the benefit index using the maslahah dharuriyah approach which contained five aspects, namely, maintaining religion, soul, mind, lineage and property, so from these five aspects concluded that the highest benefit of the Cipuy Chips UMKM in Nanggerang Village is religious maslahah with an average value of 4.9, and the lowest maslahah value is common sense with an average value of 1.7. From the descriptive qualitative analysis, it can be concluded that the perception between the employees and the surrounding community has differences regarding the benefit of the Cipuy Chips UMKM in Nanggerang Village which is influenced by age, gender, and education factors.